26 March 2021: COVID-19 vaccines advocacy and global distribution - International Livestock Research Institute (International Livestock Research Institute, 2021)
Peter Hotez, dean of the National School of Tropical Medicine at Baylor College of Medicine, talks about COVID-19 vaccines advocacy and global distribution in this interview with Eric Fevre, Professor of Veterinary and Infectious Diseases, University of Liverpool, and principal scientist at ILRI. This recording was shared on 26 March 2021. Find ILRI expertise and resources on zoonoses: ilri.org/zoonoses